UN: Seat of the Dictatorship of Powers or Symbol of Democracy? Africa and the Illusion of Seats Without Power in the Security Council. - (:unkn) unknown (My University, 2024)
The article examines the proposal to grant two permanent seats to Africa within the UN Security Council, but without the right of veto, a power held exclusively by the five major world powers. It criticizes this approach as a symbolic measure with no real impact. While Africa remains largely underrepresented in international decision-making bodies, this proposal merely adds seats without conferring any genuine influence. The article also highlights the cynicism of the great powers that advocate for democracy in their countries while refusing to share power at the international level. The veto right, seen as a tool of domination by the five permanent members, is presented as a "decision-making dictatorship" that opposes democratic principles. By refusing to extend this power to new nations, the UNSC perpetuates an imbalance in global governance. The article calls for a more ambitious reform of the Council, aimed at including Africa and other regions of the world not only in terms of seats but also in real power, to ensure a more equitable and representative international governance.
Keywords: African Research